Wija Kusuma Dance Accompaniment Music | Musik Iringan Tari Wija Kusuma - Putu Saldi (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
In socio-cultural life, especially on the islands of Bali and Indonesia in general, it will never be separated from the elements of percussion or musical art and also the art of movement or dance, these two elements cannot be separated from one another such as the concept of purusa and pradana. Likewise with the yadnya ceremony procession and the implementation of the event without being accompanied by gamelan and dance the nuances will feel much different. something that is lacking in this era of culture that used to have glory has been revived as a step for the development and preservation of a superior culture. In Bali there are many welcoming dances and other dances, this welcoming dance is used to welcome the arrival of invited guests and ceremonies either in the form of religious or artistic entertainment. Raising the title